Effectiveness and Efficiency of the Use of the Workforce Training Program Budget at the North Sumatra Provincial Manpower Office - Novitayana, Novitayana; Irawan, Irawan (UNIVED Press, 2026)
This study analyzes the effectiveness and efficiency of the use of the workforce training program budget at the North Sumatra Provincial Manpower Office through a qualitative approach. Although the average budget realization reaches 90.60%, the absorption of graduate work is still low, only 38.9% to 56.4%. Data were obtained from in-depth interviews with management officials, instructors, and trainees, as well as document reviews. The results of the study showed that 78% of respondents considered the implementation of the budget to be in accordance with administrative procedures, but only 46% stated that the training materials were in accordance with industry needs. As many as 63% of respondents assessed the limited facilities as the main obstacle to the effectiveness of the program. Research suggests planning training based on industry needs, improving facilities, and strengthening evaluations to optimize budgets.